YOU [DON’T] GOTTA PAY THE TROLL TOLL: A TRANSACTION COSTS MODEL OF ONLINE HARASSMENT - Blasiola, Stacy (AoIR Selected Papers of Internet Research, 2015)
This year’s conference theme challenges us to imagine. When it comes to the future of the internet, is it possible to imagine a space where users are free from harassment? Probably not. But it is possible to imagine spaces where the effort to harass outweighs the efforts from victims to stop the harassment. How might we begin to create this future? I propose that it starts with a reframing of the language currently used to describe these issues. In this paper I will lay out a conceptual framework for describing the processes users—both the harassed and the harassers—must go through to participate in an online environment. Given that harassment occurs across platforms, it is important that we have a way of speaking about these processes that encompasses all the potential spaces where harassment happens. Drawing from economics, I present a Transaction Cost model to describe, predict, and hopefully offer solutions to reduce online harassment.